The Sociology of Arts and Markets: New Developments and Persistent Patterns eds. A. Glauser, P. Holder, T. Mazzurana, O. Moeschler, V. Rolle, and F. Schultheis (2020), Palgrave Macmillan. - Adeyemi, Jonathan (Irish Journal of Arts Management and Cultural Policy, 2022)
The evolution of artists’ status from manual to intellectual workers during the Renaissance deters artists from demonstrating overt economic interest, which establishes the myth of art and market dichotomy and engenders the relegation of the art market in art historical studies. Through empirical studies in various artistic, historical and spatial contexts, the editors of The Sociology of Arts and Markets: New developments and persistent patterns consolidate the emergent correctives to this neglect by discussing the complex and evolving relationship between art and its markets. They justify the market’s fundamental role in the autonomisation of art, negating the grounds for the neglect of art market studies. Discernible themes in the volume include: the blurring lines between high and popular culture, exclusion, positioning, intermediation, ranking, and valuation. Re-affirming the broad relevance of Pierre Bourdieu's thinking in the sociological study of art markets, the book also demonstrates the impact of social inequalities, power relationships, and opportunities for agency in the production, mediation, and consumption of art. However, as a valuable addition to art markets studies, its neglect of the fundamental segment of art collection and reinforcement of postcolonial exclusion are shortcomings that need to be addressed in the future.